NPC photovoltaic grid-connected inverter with ride-through capability under grid faults - Dehghani Tafti, Hossein (2015)
Fault ride through (FRT) capability is one of the challenges faced in the medium to high voltage grid-tied large-scale photovoltaic (PV) power plants. This paper proposes a novel control strategy to enhance the FRT capability of a two-stage multi-string PV plant which consists of DC/DC converters and NPC inverter. The proposed control is implemented to the DC/DC converter to maintain the DC-link voltage under any grid fault conditions by adjusting the extracted PV power to the inverter output power. This is achieved by changing the PV string reference voltage from its maximum power point voltage to a new voltage point with less power. On top of that, a novel voltage-oriented control (VOC) control structure using proportional-resonant (PR) controller is proposed for the NPC inverter. Additionally, the DC-link capacitor voltages are remained balanced at all times due to the adaptive space vector modulation (ASVM) scheme. The evaluation results have verified the feasibility and the FRT capability of a 14kW PV plant using the proposed control scheme under different grid fault conditions.